Local Wisdom: A Reflection of Creativity & Innovation Through Usungan Practice in Sarawak Coastal Community - Mohamad Faizuan, Mat; Mohamad Zamhari, Abolhasan; Siti Shahida, Kamel; Sylvester, Wielding Jussem (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
The Sarawak coastal community consists of several divisions, districts and villages such as Kabong, Pusa, Spaoh, Belawai, Beladin, Maludam, Dalat and many more. A research trip has been conducted from 19-25 November 2018 in Kabong to document a rare practice by the coastal community, The marching of the Usungan. The event was held to celebrate a large group of children who completed their studies in the Al-Quran recitals. It is unique practice or tradition and it is only existing in the Borneo Island. Especially, Sarawak coastal areas continue to maintain and preserve it. Through the very interesting design of the Usungan, the Malay people of Sarawak has proven to have created their creativity and innovation. It has been stated that this practice has existed for more than 100 years ago. It is a privilege for the students or children to celebrate and, to encourage the younger generation to be successful and it is a kind of positive reinforcement for them. The Usungan also reflects the local wisdom of the people in art and design. Among the designs are aircrafts, cars, houses, mosques, boats, flowers, fishes and so on. Every design has their own story that reflects every single student who requested it. However, this practice requires the support of various parties, especially from the government, to continue and preserve it. As time goes by, some cultural heritage will be lost if no preservation effort of this practice starts from today. There are no complete and proper documentation of the design of the Usungan or any similar practice for the next generation references. Through Usungan, it shows that community knowledge in art and design in ways that can benefit the community and pass on. The event was held to celebrate a large group of children who completed their studies in the Al-Quran recitals. It is a unique practice or tradition and it only exist in the Borneo Island. Especially, Sarawak coastal areas continue to maintain and preserve it. Through the very interesting design of the Usungan, the Malay people of Sarawak has proven to have created their creativity and innovation.